CITRA PEREMPUAN DAN GAYA BAHASA DALAM KUMPULAN PUISI IBU MENDULANG ANAK BERLARI SEBAGAI MATERI PEMBELAJARAN SASTRA - Novena, Yuvensia Kharisma; Suhita, Raheni; Suryanto, Edy (Universitas Sebelas Maret, 2020)
This research has purpose to describe and explain; (1) The position of woman figure in collection of poetry Ibu Mendulang Anak Berlari by Cyntha Hariadi. (2) The language style of Poetry in Ibu Mendulang Anak Berlari. (3) The collection of poetry Ibu Mendulang Anak Berlari that can be used in a poetry learning material in senior high school. This research used the method of qualitative. Data analysis of this research used interaktif analysis within 3 components: data reducing, Data validity test is done by triangulating theory and triangulation of the data source. Based on the results of the study can be concluded: (1) on the poetry collection of ibu mendulang anak berlari has (a) Physical figure, (b) Physcological Figure, and (c) Social Figure; (2) Repetition is the most dominant style that used in the Ibu Mendulang Anak berlari poetry collection; (3) Ibu Mendulang Anak Berlari poetry collection can be used as a poetry learning material in senior high school, especially on KD 3.16 (Identifying the atmosphere, theme, and the meaning of poetry that has been read) and KD 3.17 (Analyze the elements of poetry).